CLASSIFICATION OF ACCOUNTANCY SERVICES. - Wildman, John R. (The Accounting Review, 1928)
Abstract Accountancy practice in this country has grown from a theoretical zero to an institution comprising, probably, 25,000 public accountants, and gross annual earnings estimated at from $ 350,000,000 to $100,000,000. Twenty-five years ago engagements were taken, work was performed, reports were prepared and rendered, bills were paid, and few, if any, questions were asked by clients. This condition may be attributed largely, perhaps, to the fact that clients had little knowledge of accounting, or of auditing, or of what the accountants were supposed to do. Today, the accountant's relation to business, and to the personnel of business is quite different. For twenty-five years university schools teaching accounting and other subjects have been pouring their products into the business world. These men have taken positions as accountants, company auditors, treasurers, comptrollers, and credit men. Some of them have risen to the ranks of presidents, vice presidents, secretaries, and chairmen of finance committee. Not a few have become substantial shareholders.